2004
DOI: 10.1007/bf03030858
|View full text |Cite
|
Sign up to set email alerts
|

Identification of groundwater prospective zones using irs-id liss iii and pump test methods

Abstract: The role of hydrogeomorphological units and lineaments in tile storage of groundwater from the Muvattupuzha river basin has been investigated using IRS ID LISS Ill data. Other than the usual water bodies such as river course, reservoirs and ponds, the major hydrogeomorphologica[ units identified in this basin in the descending order of their groundwater potential are: valley fills, moderately dissected plateau, pediments, residual mounts, residual mount complex, linear ridges, residual hills and structural hil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Application of RS in hydrogeological investigation and monitoring can provide significant information in spatial and temporal scales, which is important for effective analysis, prediction, and validation of water resources models [33]. The ability of satellite imagery to cover large spatial scales is essential for the depiction of basins physiographic characteristics, such as land use/land cover, slope, and drainage density as well as structural characteristics such as fractures, faults, and cleavages [34][35][36][37][38][39]. Such characteristics are major requirements for groundwater resources evaluation and exploration and were used by many researchers (e.g., Table 2) for GWPZs delineation.…”
Section: Introductionmentioning
confidence: 99%
“…Application of RS in hydrogeological investigation and monitoring can provide significant information in spatial and temporal scales, which is important for effective analysis, prediction, and validation of water resources models [33]. The ability of satellite imagery to cover large spatial scales is essential for the depiction of basins physiographic characteristics, such as land use/land cover, slope, and drainage density as well as structural characteristics such as fractures, faults, and cleavages [34][35][36][37][38][39]. Such characteristics are major requirements for groundwater resources evaluation and exploration and were used by many researchers (e.g., Table 2) for GWPZs delineation.…”
Section: Introductionmentioning
confidence: 99%
“…The overlay analysis of the spatial analyst tool of ArcGIS 10.3 applied to prepare the final map is one of the foremost methods of integrating multiple thematic layers (Fig. S1) having a common computational scale (Gopinath and Seralathan 2004). The SESZ was calculated using Eq.…”
Section: Soil Erosion-susceptible Zone (Sesz)mentioning
confidence: 99%
“…Hydro geomorphology was used by authors such as József (1999); Sankar (2002); Sikdar, Chakraborty, Adhya, and Paul ( 2004); Gopinath and Seralathan (2004); (Sujarose & Krishnan, 2009); Murugesan, Krishnaraj, Kannusamy, Selvaraj, and Subramanya (2011) to delineate water potential areas. The predominant terrain in the study region is plains, as shown by Pediplain and hills.…”
Section: Geomorphologymentioning
confidence: 99%